Carbon Thin-Film Electrodes as High-Performing Substrates for Correlative Single Entity Electrochemistry - Colavita, Paula; Nicolosi, Valeria (My University, 2025)
Correlative methods to characterize single entities by electrochemistry and microscopy/spectroscopy are increasingly needed to elucidate structure-function relationships of nanomaterials. However, the technical constraints often differ depending on the characterization techniques to be applied in combination. One of the cornerstones of correlative single-entity electrochemistry (SEE) is the substrate, which needs to achieve a high conductivity, low roughness, and electrochemical inertness. This work shows that graphitized sputtered carbon thin films constitute excellent electrodes for SEE while enabling characterization with scanning probe, optical, electron, and X-ray microscopies. Three different correlative SEE experiments using nanoparticles, nanocubes, and 2D Ti3C2Tx MXene materials are reported to illustrate the potential of using carbon thin film substrates for SEE characterization. The advantages and unique capabilities of SEE correlative strategies are further demonstrated by showing that electrochemically oxidized Ti3C2Tx MXene display changes in chemical bonding and electrolyte ion distribution
PUBLISHED
Keywords: nanomaterials; SEE correlative strategies; Ti3C2Tx MXene display; nanomaterials; SEE correlative strategies; Ti3C2Tx MXene display; Nanoscience & Materials